Analysis of risk factors in breast cancer patients with hand-foot syndrome and oral mucositis caused by pegylated liposomal doxorubicin - Xianghua Quan; Jing Li; Jialin Sun; Xiaomin Xing; Donghua Liu; Hongyan Ji; Qie Guo (Frontiers in Oncology)
IntroductionDoxorubicin (DOX) is a primary treatment for breast cancer (BC), but its widespread use is hindered by cardiotoxicity. Pegylated liposomal doxorubicin (PLD) has been developed to enhance the efficacy of DOX and mitigate its cardiotoxic effects. However, PLD is associated with adverse reactions (ADRs) such as hand-foot syndrome (HFS) and oral mucositis (OM), which have garnered significant attention. Although not life-threatening, HFS and OM can cause severe discomfort and functional impairment. Severe cases may necessitate a reduced PLD dose or even delay or interrupt chemotherapy, ultimately leading to decreased medication compliance. Here, we conduct an analysis of the risk factors associated with HFS and OM during the PLD chemotherapy regimen, thus providing early warning indicators for the potential occurrence of these adverse reactions in BC patients.MethodsIn this study, a total of 395 BC patients receiving PLD chemotherapy were enrolled. Follow-up observations towards the baseline and clinical characteristics in these patients were exhibited. The evaluation of HFS and OM in these patients was also performed based on the Common Terminology Criteria for Adverse Events (CTCAE) Version 5.0. Analysis of factors influencing simultaneous incidence of HFS and OM was executed using the univariate analysis and multivariate logistic regression analysis.ResultsDose intensity, history of cholelithiasis, ALT, AST, and Hb were identified as related risk factors for HFS. Dose intensity and reductions in white blood cell (WBC) counts were associated with the risk of OM. Furthermore, increased dose intensity, decreased WBC counts, and a history of cholelithiasis emerged as independent risk factors for the concurrent occurrence of HFS and OM.DiscussionThis study investigated the various risk factors related to HFS, OM, and their combination in BC patients undergoing PLD chemotherapy, offering insights for the prevention and treatment of BC and other cancers.